2022
DOI: 10.14336/ad.2022.0131
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Movement and Eating Behaviours in Brazilian Elderly: An Analysis of Clusters Associated with Disease Outcomes

Abstract: Aging is a biological process, which is usually associated with health-related problems, which are related to some behaviours, such as those related to movement and eating habits. So, the purpose of the present study was to identify the clustering of behavioural and eating habits related to non-communicable disease in Brazilian elderly, and to estimate the association of these profiles with overweight/obesity, hypertension, and diabetes. This is a cross-sectional based-population study, which sample comes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Comparing this directly with other data-driven clustering studies is complicated since the limited number of papers that has focused on health behaviors in older adults assessed these health behaviors differently (e.g., TV time instead of sitting time as a measure of sedentary behavior; fruit and vegetable consumption rather than an overall food score) [43]. Despite this, the current study seems to contrast the results from a self-reported study in an elderly cohort (mean age = 71 years) [44], who found that nutrition was the most distinct health behavior, and that movement behaviors were similar. On the other hand, our findings are in line with a study in ~ 40-70-year-olds [45] that found that movement behaviors (prolonged sitting and being physically inactive) clustered within classes, but alcohol intake was similar.…”
Section: Discussionmentioning
confidence: 71%
“…Comparing this directly with other data-driven clustering studies is complicated since the limited number of papers that has focused on health behaviors in older adults assessed these health behaviors differently (e.g., TV time instead of sitting time as a measure of sedentary behavior; fruit and vegetable consumption rather than an overall food score) [43]. Despite this, the current study seems to contrast the results from a self-reported study in an elderly cohort (mean age = 71 years) [44], who found that nutrition was the most distinct health behavior, and that movement behaviors were similar. On the other hand, our findings are in line with a study in ~ 40-70-year-olds [45] that found that movement behaviors (prolonged sitting and being physically inactive) clustered within classes, but alcohol intake was similar.…”
Section: Discussionmentioning
confidence: 71%